Sulfur-carbon composite, positive electrode for lithium-sulfur battery comprising the sulfur-carbon composite, and lithium-sulfur battery comprising the positive electrode

By using sulfur-carbon composites coated with specific monomer copolymers in lithium-sulfur batteries, the problems of low lithium ion conductivity and short battery life in lithium-sulfur batteries are solved, and better battery reactivity and life are achieved.

CN113853698BActive Publication Date: 2025-04-29LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080035203.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-31
Filing Date
2020-05-29
Publication Date
2025-04-29
Estimated Expiration
2040-05-29

AI Technical Summary

Technical Problem

In lithium-sulfur batteries, due to the low conductivity of sulfur and the side reactions caused by the electrolyte on the surface of carbon materials, lithium ion conductivity and battery life are reduced.

Method used

The adhesion and lithium ion conductivity of the carbon material are improved by coating the copolymer by using a sulfur-carbon composite containing a monomer having a functional group well bonded to the carbon surface and a monomer having excellent lithium ion conductivity.

Benefits of technology

It effectively solves the side reaction problems caused by electrolyte and lithium polysulfide on the surface of carbon materials, improves lithium ion conductivity, and thus improves the reactivity and life characteristics of lithium-sulfur batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113853698B_ABST
    Figure CN113853698B_ABST
Patent Text Reader

Abstract

The present invention provides a sulfur-carbon composite comprising sulfur and a carbon material coated with a coating material comprising a copolymer comprising a monomer containing a catechol group and a monomer containing a lithium ion conductor; an electrode for a lithium-sulfur battery comprising the sulfur-carbon composite; and a lithium-sulfur battery comprising the electrode as described above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2019-0064310 filed on May 31, 2019 and Korean Patent Application No. 10-2020-0064835 filed on May 29, 2020, which are hereby incorporated by reference in their entirety.

[0002] The present invention relates to a sulfur-carbon composite, a positive electrode for a lithium-sulfur battery comprising the sulfur-carbon composite, and a lithium-sulfur battery comprising the positive electrode. Background Art

[0003] As the use range of lithium secondary batteries expands not only to portable electronic devices and communication devices but also to electric vehicles (EVs) and power storage systems (ESSs), demand for high capacity of lithium secondary batteries used as their power sources is increasing.

[0004] A lithium-sulfur battery among various lithium secondary batteries is a secondary battery using a sulfur-based material having a sulfur-sulfur bond as a positive electrode active material and using lithium metal, a carbon-based material in which insertion / extraction of lithium ions occurs, or silicon or tin alloyed with lithium as a negative electrode active material.

[0005] The lithium-sulfur battery has advantages in that sulfur, which is a main material of a positive electrode active material in the lithium-sulfur battery, has a low atomic weight, is very abundant in resources and is therefore easy to supply and receive, and is inexpensive, non-toxic, and environmentally friendly.

[0006] Since the theoretical energy density of lithium-sulfur batteries is much higher than that of other battery systems (Ni-MH battery: 450Wh / kg; Li-FeS battery: 480Wh / kg; Li-MnO2 battery: 1000Wh / kg; Na-S battery: 800Wh / kg) and commercially available lithium secondary batteries (LiCoO2 / graphite), lithium-sulfur batteries have attracted attention as a high-capacity, environmentally friendly and low-cost lithium secondary battery.

[0007] In lithium-sulfur batteries, sulfur, used as the positive electrode active material, has a 5×10 -30 S / cm and is therefore a non-conductor with no electrical conductivity, so there is a problem that electrons generated by electrochemical reactions are difficult to move. Therefore, it is used in combination with a conductive material such as carbon that can provide an electrochemical reaction site.

[0008] However, although the initial capacity of lithium-sulfur batteries is high in actual operation, it is difficult to ensure sufficient performance and operational stability because the capacity and charge / discharge efficiency characteristics decrease rapidly as the cycle progresses and the life is also shortened, and therefore lithium-sulfur batteries have not yet been commercialized. The reason is that sulfur is lost due to the dissolution of lithium polysulfide, which is an intermediate product generated during the electrochemical reaction of the lithium-sulfur battery, and can no longer participate in the charge / discharge reaction of the battery, and the electrolyte causes a side reaction on the surface of the carbon material to shorten the life, or the dissolved lithium polysulfide is isolated and can no longer participate in the reaction.

[0009] In order to solve the problem that the electrolyte causes side reactions on the surface of the carbon material and allow lithium ions to smoothly approach carbon and react with sulfur, attempts have been made to prevent decomposition of the electrolyte on the carbon surface and increase lithium ion conductivity by using an organic protective material.

[0010] However, in the case of a protective material having no interaction with the surface of carbon, there is a problem that its mixing is merely physical mixing, and over time, it is physically separated from the surface of carbon and produces an adverse effect of acting as a resistance component.

[0011] Furthermore, in order to solve the above-mentioned problems, attempts have been made to increase the binding force of the organic protective material by introducing -OH or -COOH groups into aromatic carbon on the carbon / graphite surface.

[0012] However, there is a disadvantage that when the surface of carbon / graphite as described above is modified using a high-energy plasma treatment or UV / ozone treatment method, oxidation mainly occurs at the edge portion of the carbon / graphite, so the hydrophilic modification effect is low, and instead, the conjugated network is destroyed (double bonds are converted into single bonds), thereby deteriorating the conductivity.

[0013] [Prior art literature]

[0014] [Patent Document]

[0015] Korean Patent Publication No. 10-2018-0033665 Summary of the invention

[0016]

Technical issues

[0017] The inventors of the present invention have made great efforts to solve the above-mentioned problems in the prior art, and have found that when a copolymer containing a monomer having a functional group that bonds well to a carbon surface and a monomer having excellent lithium ion conductivity is used, the above-mentioned problems can be solved, and thus the present invention has been completed.

[0018] Therefore, an object of the present invention is to provide a sulfur-carbon composite which does not have the problem of electrolyte and lithium polysulfide causing side reactions on the surface of carbon material and has excellent lithium ion conductivity, thereby improving the reactivity and life characteristics of lithium-sulfur batteries.

[0019] In addition, another object of the present invention is to provide a positive electrode for a lithium-sulfur battery including the sulfur-carbon composite and a lithium-sulfur battery having excellent reactivity and life characteristics.

[0020]

Technical solution

[0021] To achieve the above object, the present invention provides a sulfur-carbon composite comprising: a carbon material coated with a copolymer comprising a monomer containing a catechol group and a monomer containing a lithium ion conductor; and sulfur.

[0022] In one embodiment of the present invention, the copolymer may be represented by the following formula 1:

[0023] [Formula 1]

[0024]

[0025] in

[0026] R1 and R2 are each independently hydrogen or methyl,

[0027] a and b represent the molar ratio of each monomer, a is 1 to 5, and b is 5 to 9; and

[0028] n is a natural number ranging from 1 to 20.

[0029] In addition, the present invention provides a positive electrode for a lithium-sulfur battery, which comprises the sulfur-carbon composite of the present invention.

[0030] In addition, the present invention provides a lithium-sulfur battery, which comprises a positive electrode; a negative electrode; a separator and an electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode is the positive electrode of the present invention.

[0031]

Beneficial Effects

[0032] The sulfur-carbon composite of the present invention is prepared using a carbon material coated with a copolymer containing a monomer containing a catechol group and a monomer containing a lithium ion conductor, thereby effectively solving the problem of side reactions caused by electrolyte and lithium polysulfide on the surface of the carbon material of the sulfur-carbon composite.

[0033] Furthermore, the sulfur-carbon composite of the present invention is free from the above-mentioned problems and has excellent lithium ion conductivity, thereby providing the effect of improving the reactivity and life characteristics of a lithium-sulfur battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a graph showing the measurement results of the life characteristics of a battery using the sulfur-carbon composite of the present invention.

[0035] Figure 2 Graphs showing the results of measurements of reactivity and life characteristics of a battery using a conventional sulfur-carbon composite.

[0036] Figure 3 It is a graph showing the results of measuring the reactivity and life characteristics of a battery using the sulfur-carbon composite whose surface is coated with the copolymer used in the present invention.

[0037] Figure 4 and Figure 5 The graphs show the results of measuring the reactivity and life characteristics of batteries using the sulfur-carbon composite of the present invention and conventional sulfur-carbon composites. DETAILED DESCRIPTION

[0038] Hereinafter, the present invention will be described in detail.

[0039] The present invention relates to a sulfur-carbon composite comprising: a carbon material coated with a copolymer comprising a monomer containing a catechol group and a monomer containing a lithium ion conductor; and sulfur.

[0040] Generally, since a carbon material is a material having extremely low polarity, it cannot be well coated with an organic protective material, and even if coated, the coating material is easily physically peeled off.

[0041] The present invention is characterized in that a solution to the above-mentioned problem is provided. That is, the coating copolymer of the present invention contains a hydrophilic copolymer containing a monomer containing a catechol group as a binding material derived from mussels, and thereby provides excellent adhesion to the surface of a carbon material. That is, the catechol group adheres well to any surface, in particular, even to the surface of carbon-based or graphite-based particles. In addition, the coating copolymer of the present invention contains a monomer containing a lithium ion conductor, thereby providing a feature of improving lithium ion conductivity.

[0042] In the present invention, "a carbon material coated with a copolymer containing a monomer containing a catechol group and a monomer containing a lithium ion conductor" should be understood as a concept including a carbon material coated with a coating composition containing the copolymer. In the case of the coating composition, in addition to the copolymer, known components such as a solvent and a binder commonly used in the art may be contained in a usual composition ratio.

[0043] In the copolymer, the molar ratio of the monomer containing a catechol group to the monomer containing a lithium ion conductor may be 1-5:5-9, more preferably 1-3:7-9, and more preferably 2-3:7-8.

[0044] Specifically, if the molar ratio of the monomer containing a catechol group is outside the above range and is therefore insufficient, there may be a problem of insufficient adhesion to the carbon material. If the molar ratio of the monomer containing a lithium ion conductor is outside the above range and is therefore insufficient, there may be a problem of reduced lithium ion conductivity. If each component is excessively contained outside the above range, the opposite problem to the above may occur, which is not preferred.

[0045] As the monomer containing a lithium ion conductor, a monomer having lithium ion conductivity and polymerizable with a monomer containing a catechol group can be used.

[0046] The monomer containing a lithium ion conductor may be a monomer containing at least one selected from an ethyleneoxy group, a sulfone group, etc. The monomer may be a monomer containing a vinyl group, and may be, for example, a (meth)acrylic monomer.

[0047] More specifically, the monomer containing a lithium ion conductor may be a polyethylene glycol methyl ether (meth)acrylate monomer or the like.

[0048] The number of repeating units of the ethyleneoxy group contained in the polyethylene glycol methyl ether group contained in the polyethylene glycol methyl ether (meth)acrylate monomer may be 1-20, and more preferably 1-10.

[0049] If the number of repeating units of ethyleneoxy is less than the above range, there may be a problem of insufficient lithium ion conductivity. If the number of repeating units of ethyleneoxy exceeds the above range, there may be a problem of increased resistance of the electrode.

[0050] The portion described as "(meth)acrylate" should be interpreted as a concept including methacrylate and acrylate.

[0051] The copolymer may have a weight average molecular weight of 5000 to 1000000, more preferably 150000 to 300000, and particularly preferably 200000 to 300000. If the weight average molecular weight is less than the above range, there may be a problem of insufficient adhesion to the carbon material. If the weight average molecular weight exceeds the above range, there may be a problem of increased resistance of the electrode, which is not preferred.

[0052] It may be preferred that the copolymer is a random copolymer because when each monomer is distributed as evenly as possible, better lithium ion conductivity and adhesion can be exhibited.

[0053] The monomer containing a catechol group may be a vinyl monomer, such as a dopamine (meth) acrylamide monomer.

[0054] Specifically, the copolymer may be a copolymer represented by the following Formula 1:

[0055] [Formula 1]

[0056]

[0057] in

[0058] R1 and R2 are each independently hydrogen or methyl,

[0059] a and b represent the molar ratio of each monomer, and a is 1 to 5, and b is 5 to 9; and

[0060] n is a natural number ranging from 1 to 20.

[0061] The molar ratio of a to b of the copolymer represented by Formula 1 is more preferably 1-3:7-9, and more preferably 2-3:7-8.

[0062] If the molar ratio of a to b is outside the above range, specifically, if the molar ratio of the monomer containing a catechol group is outside the above range and is therefore insufficient, there may be a problem of insufficient adhesion to the carbon material. If the molar ratio of the polyethylene glycol methyl ether (meth) acrylate monomer is outside the above range and is therefore insufficient, there may be a problem of reduced lithium ion conductivity. If each component is excessively contained outside the above range, the opposite problem to the above may occur, which is not preferred.

[0063] n may be a natural number of 1-20, more preferably 1-10, and particularly preferably 1-5.

[0064] If the value of n is smaller than the above range, there may be a problem that lithium ion conductivity is insufficient. If the value of n exceeds the above range, there may be a problem that the resistance of the electrode increases.

[0065] The copolymer may have a weight average molecular weight of 5000 to 1000000, more preferably 150000 to 300000, and particularly preferably 200000 to 300000. If the weight average molecular weight is less than the above range, there may be a problem of insufficient adhesion to the carbon material. If the weight average molecular weight exceeds the above range, there may be a problem of increased resistance of the electrode, which is not preferred.

[0066] The copolymer represented by Formula 1 can be prepared based on the following Reaction Formula 1:

[0067] [Reaction 1]

[0068]

[0069] Specifically, first, the polymerization inhibitor of polyethylene glycol methyl ether (meth) acrylate monomer is removed using column chromatography filled with basic alumina. The polymerization inhibitor refers to an additive added at a level of 100 ppm to prevent self-photocuring or thermal curing of polyethylene glycol methyl ether (meth) acrylate monomer, and for example, may be BHT (2,6-di-tert-butyl-4-methylphenol) and MEHQ (4-methoxyphenol).

[0070] After a solvent such as DMF (dimethylformamide) is added to the reactor, purified polyethylene glycol methyl ether (meth)acrylate monomer, dopamine (meth)acrylamide monomer, and a polymerization initiator are added.

[0071] Next, the reaction mixture is degassed with nitrogen and then reacted at 40° C. to 80° C. for 10 hours to 25 hours while stirring.

[0072] When the reaction is completed, the product is precipitated using n-hexane or the like to obtain a copolymer.

[0073] The carbon material used to prepare the sulfur-carbon composite of the present invention may be at least one selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon fibers, carbon nanobelts, carbon nanorods, carbon nanorods, activated carbon, and the like.

[0074] The carbon material may preferably be a porous carbon material.

[0075] In the sulfur-carbon composite of the present invention, it can have a weight ratio of copolymer to carbon material in the range of 0.1:99.9 to 5:95, more preferably 0.5:99.5 to 3:97, especially preferably 0.5:99.5 to 2:98, and particularly preferably 0.5:99.5 to 1.5:98.5, wherein the copolymer comprises a monomer containing a catechol group and a monomer containing a lithium ion conductor.

[0076] If the copolymer is contained below the above range, it is difficult to effectively prevent the side reaction of the electrolyte and lithium polysulfide. If the copolymer exceeds the above range, the reactivity and life characteristics of the battery may be deteriorated, which is not preferred.

[0077] In the sulfur-carbon composite of the present invention, the sulfur may be selected from inorganic sulfur, Li2S n At least one of the group consisting of (n≥1), disulfide compounds, organic sulfur compounds, carbon-sulfur polymers, and the like.

[0078] The sulfur-carbon composite of the present invention may contain 10 to 50 wt %, preferably 20 to 40 wt %, of a carbon material based on the total weight of the sulfur-carbon composite. The carbon material may preferably be a porous carbon material.

[0079] The sulfur-carbon composite of the present invention may contain sulfur in an amount of 50 to 90 wt %, preferably 60 to 80 wt %, based on the total weight of the sulfur-carbon composite.

[0080] Therefore, the weight ratio of the carbon material to sulfur in the sulfur-carbon composite of the present invention may be 5:5 to 9:1, preferably 7:3 to 9:1.

[0081] If the content of sulfur is less than the above range, as the content of the porous carbon material of the sulfur-carbon composite increases relatively, the specific surface area increases, and therefore, the content of the binder increases when preparing the slurry. The increase in the amount of the binder used may eventually increase the sheet resistance of the positive electrode, and thus may act as an insulator that prevents electrons from passing through, thereby deteriorating the performance of the battery. On the contrary, if the content of sulfur exceeds the above range, the sulfur that is not combined with the porous carbon material will aggregate with each other or dissolve again to the surface of the porous carbon material, and therefore may be difficult to receive electrons and cannot participate in the electrochemical reaction, resulting in battery capacity loss.

[0082] Furthermore, the present invention relates to a positive electrode for a lithium-sulfur battery, comprising the sulfur-carbon composite of the present invention.

[0083] In the positive electrode, for configurations other than the sulfur-carbon composite of the present invention, techniques known in the art may be applied without limitation.

[0084] The sulfur-carbon composite may be included in the positive electrode as a positive electrode active material.

[0085] In addition to the positive electrode active material, the positive electrode may further include one or more additives selected from transition metal elements, Group IIIA elements, Group IVA elements, sulfur compounds of these elements, and alloys of these elements with sulfur.

[0086] The transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., the IIIA group elements may include Al, Ga, In, Tl, etc., and the IVA group elements may include Ge, Sn, Pb, etc.

[0087] The positive electrode may further include, in addition to the positive electrode active material or optional additives, a conductive material for smoothly moving electrons within the positive electrode and a binder for well adhering the positive electrode active material to a current collector.

[0088] The conductive material is a material that electrically connects the electrolyte and the cathode active material to serve as a path for electrons to move from the current collector to the cathode active material, and may be used without limitation as long as it has conductivity.

[0089] For example, the conductive material may include carbon blacks such as Super-P, Denka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon black, alone or in combination of two or more; carbon derivatives such as carbon nanotubes or fullerenes; conductive fibers such as carbon fibers and metal fibers; fluorinated carbon; metal powders such as aluminum powder and nickel powder; or conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole.

[0090] The conductive material may be added in an amount of 0.01 wt % to 30 wt % based on the total weight of the mixture containing the positive electrode active material.

[0091] The binder is used to maintain the positive electrode active material on the positive electrode current collector and to organically connect the positive electrode active materials to increase the binding force therebetween. As the binder, any binder known in the art may be used.

[0092] The content of the binder may be added in an amount of 0.5 wt % to 30 wt % based on the total weight of the mixture containing the positive electrode active material. If the content of the binder is less than 0.5 wt %, the physical properties of the positive electrode are reduced and the active material and the conductive material in the positive electrode may fall off. If the content of the binder exceeds 30 wt %, the ratio of the active material to the conductive material in the positive electrode is relatively reduced, and thus the capacity of the battery may be reduced.

[0093] The positive electrode can be prepared by conventional methods known in the art.

[0094] In addition, the present invention relates to a lithium-sulfur battery, comprising a positive electrode; a negative electrode; a separator and an electrolyte disposed between the positive electrode and the negative electrode, wherein the positive electrode is the positive electrode of the present invention.

[0095] In the lithium-sulfur battery, for other configurations than the sulfur-carbon composite of the present invention, techniques known in the art may be applied without limitation.

[0096] The negative electrode may be composed of a current collector and a negative electrode active material layer formed on one or both surfaces thereof. In addition, the negative electrode may be a lithium metal plate.

[0097] The current collector is used to load the negative electrode active material and is not particularly limited as long as it is electrochemically stable within the voltage range of the lithium secondary battery while having excellent conductivity, and for example, copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon; or copper or stainless steel whose surface has been treated with carbon, nickel, silver, etc.; or aluminum-cadmium alloy, etc. can be used.

[0098] The negative electrode current collector may improve the binding force with the negative electrode active material by having fine concavities and convexities on its surface, and may be formed in various forms such as a film, a sheet, a foil, a mesh, a net, a porous body, a foam, or a nonwoven fabric.

[0099] The negative electrode active material may include a material that can reversibly insert or release lithium ions (Li + ) material; a material capable of reacting with lithium ions to reversibly form a lithium-containing compound; or lithium metal or a lithium alloy.

[0100] Able to reversibly insert or deintercalate lithium ions (Li + ) can be crystalline carbon, amorphous carbon or a mixture thereof. + ) to reversibly form a lithium-containing compound, for example, tin oxide, titanium nitrate or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al) and tin (Sn).

[0101] Preferably, the negative electrode active material may be lithium metal, specifically in the form of lithium metal film or lithium metal powder.

[0102] A separator is additionally included between the positive electrode and the negative electrode. The separator allows lithium ions to be transported between the positive electrode and the negative electrode while separating or insulating the positive electrode and the negative electrode from each other. The separator can be made of a porous, non-conductive or insulating material. The separator can be an independent component such as a film, or a coating added to the positive electrode and / or the negative electrode.

[0103] The material constituting the separator includes, but is not limited to, for example, polyolefins such as polyethylene and polypropylene; glass fiber filter paper and ceramic materials, and its thickness may be about 5 μm to about 50 μm, preferably about 5 μm to about 25 μm.

[0104] The electrolyte is located between the positive electrode and the negative electrode and contains a lithium salt and a non-aqueous organic solvent.

[0105] Depending on various factors, such as the exact composition of the electrolyte, the solubility of the salt, the conductivity of the dissolved salt, the charging and discharging conditions of the battery, the operating temperature and other factors known in the field of lithium batteries, the concentration of the lithium salt can be 0.2M to 2M, preferably 0.6M to 2M, and more preferably 0.7M to 1.7M. If the concentration of the lithium salt is less than 0.2M, the conductivity of the electrolyte may decrease and thus the performance of the electrolyte may deteriorate. If the concentration of the lithium salt exceeds 2M, the viscosity of the electrolyte may increase and thus the mobility of lithium ions may decrease.

[0106] The lithium salt is not particularly limited as long as it can be conventionally used in lithium-sulfur battery electrolytes. For example, the lithium salt can be selected from LiSCN, LiBr, LiI, LiPF6, LiBF4, LiB 10 Cl 10 , LiSO3CF3, LiCl, LiClO4, LiSO3CH3, LiB(Ph)4, LiC(SO2CF3)3, LiN(SO2CF3)2, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, LiFSI, lithium chloroborane, lower aliphatic carboxylate lithium, etc.

[0107] As the non-aqueous organic solvent, those conventionally used in lithium secondary battery electrolytes can be used without restriction. For example, the organic solvent can include ethers, esters, amides, linear carbonates, cyclic carbonates, etc., alone or in a combination of two or more. Among them, representatively, ether compounds can be included.

[0108] For example, the ether compound can be, but is not limited to, at least one selected from the group consisting of dimethyl ether, ethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, polyethylene glycol methyl ethyl ether, 1,3-dioxolane, tetrahydrofuran and 2-methyltetrahydrofuran.

[0109] Examples of esters in the organic solvent may include, but are not limited to, at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone, and a mixture of two or more thereof.

[0110] Specific examples of the linear carbonate compound may representatively include, but are not limited to, at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, or a mixture of two or more thereof.

[0111] In addition, specific examples of the cyclic carbonate compound may include any one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate and halides thereof, or a mixture of two or more thereof.

[0112] Examples of such halides include, but are not limited to, fluoroethylene carbonate (FEC) and the like.

[0113] In addition to the above-mentioned organic solvents, N-methylpyrrolidone, dimethyl sulfoxide, sulfolane, etc. can also be used.

[0114] In addition to the above components, the electrolyte may also include nitric acid compounds commonly used in the relevant field. Examples thereof may include lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), magnesium nitrate (Mg(NO3)2), barium nitrate (Ba(NO3)2), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), etc.

[0115] The injection of the electrolyte can be performed at an appropriate stage in the manufacturing process of the electrochemical device, depending on the manufacturing process and the desired properties of the final product. That is, the injection can be performed before assembling the electrochemical device or at the final stage of assembling the electrochemical device.

[0116] In addition to the usual winding process, the lithium-sulfur battery according to the present invention can also be manufactured through lamination, stacking and folding processes of the separator and the electrode.

[0117] The shape of the lithium-sulfur battery is not particularly limited, and may be various shapes such as a cylindrical shape, a laminated shape, and a coin shape.

[0118] Hereinafter, preferred embodiments are provided to help understand the present invention, but the following embodiments merely illustrate the present invention, and it is obvious to those skilled in the art that various changes and modifications can be made within the scope and technical spirit of the present invention, and these changes and modifications naturally belong to the appended claims.

[0119] Preparation Example 1: Preparation of a copolymer represented by Formula 1 (monomer molar ratio 3:7)

[0120] The polymerization inhibitor was removed from 12.5 ml of polyethylene glycol methyl ether acrylate (PEGMEA) by column chromatography filled with 30 g of basic alumina.

[0121] After 20 ml of DMF was added to a 500 ml double-necked round-bottom flask, 7.5 g of purified PEGMEA (Mn=480), 1.7 g of dopamine methacrylamide (DMA) and 106 mg of azobisisobutyronitrile were dissolved in DMF. After the reaction mixture was degassed with N2 (gas) for 10 minutes, the mixture was stirred at 60 ° C for 17 hours. After the reaction was completed, the reaction product was precipitated in a 1000 ml beaker using 800 ml of n-hexane to obtain a poly-DMA-PEGMEA copolymer with a monomer molar ratio of 3:7 and a weight average molecular weight of 250,000.

[0122] Preparation Example 2: Preparation of a copolymer represented by Formula 1 (monomer molar ratio 5:5)

[0123] The polymerization inhibitor was removed from 12.5 ml of polyethylene glycol methyl ether acrylate (PEGMEA) by column chromatography filled with 30 g of basic alumina.

[0124] After 20 ml of DMF was added to a 500 ml double-necked round-bottom flask, 10 g of purified PEGMEA (Mn=480), 1.2 g of dopamine methacrylamide (DMA) and 106 mg of azobisisobutyronitrile were dissolved in DMF. After the reaction mixture was degassed with N2 (gas) for 10 minutes, the mixture was stirred at 60 ° C for 17 hours. After the reaction was completed, the reaction product was precipitated in a 1000 ml beaker using 800 ml of n-hexane to obtain a poly-DMA-PEGMEA copolymer with a monomer molar ratio of 5:5 and a weight average molecular weight of 250,000.

[0125] Preparation Example 3: Preparation of poly-DMA-PEGMEA copolymer coated carbon material (monomer molar ratio = 3:7)

[0126] 10 g of the polyDMA-PEGMEA copolymer prepared in Preparation Example 1 was dissolved in 90 g of distilled water to prepare a coating agent having a concentration of 10 wt %, which was then diluted to be used as a coating agent.

[0127] The coating agent was mixed with 10 g of carbon nanotubes (trade name: Multiwall CNT, manufacturer: Aldrich) to prepare a polyDMA-PEGMEA copolymer-coated carbon material (weight ratio of carbon material:polyDMA-PEGMEA copolymer=99:1).

[0128] Preparation Example 4: Preparation of polyDMA-PEGMEA copolymer coated carbon material (monomer molar ratio = 3:7)

[0129] 10 g of the polyDMA-PEGMEA copolymer prepared in Preparation Example 1 was dissolved in 90 g of distilled water to prepare a coating agent having a concentration of 10 wt %, which was then diluted to be used as a coating agent.

[0130] The coating agent was mixed with 10 g of carbon nanotubes (trade name: Multiwall CNT, manufacturer: Aldrich Corporation) to prepare a polyDMA-PEGMEA copolymer-coated carbon material (weight ratio of carbon material:polyDMA-PEGMEA copolymer=98:2).

[0131] Preparation Example 5: Preparation of polyDMA-PEGMEA copolymer coated carbon material (monomer molar ratio = 5:5)

[0132] 10 g of the polyDMA-PEGMEA copolymer prepared in Preparation Example 2 was dissolved in 90 g of distilled water to prepare a coating agent having a concentration of 10 wt %, which was then diluted to be used as a coating agent.

[0133] The coating agent was mixed with 10 g of carbon nanotubes (trade name: Multiwall CNT, manufacturer: Aldrich Corporation) to prepare a polyDMA-PEGMEA copolymer-coated carbon material (weight ratio of carbon material:polyDMA-PEGMEA copolymer=99:1).

[0134] Example 1: Preparation of sulfur-carbon composite

[0135] The polyDMA-PEGMEA copolymer-coated carbon material prepared in Preparation Example 3 and sulfur (S8) were uniformly mixed at a weight ratio of 3:7, placed in an oven at 155° C. and treated for 30 minutes to prepare a sulfur-carbon composite.

[0136] Example 2: Preparation of sulfur-carbon composite

[0137] The polyDMA-PEGMEA copolymer-coated carbon material prepared in Preparation Example 4 and sulfur (S8) were uniformly mixed at a weight ratio of 3:7, placed in an oven at 155° C. and treated for 30 minutes to prepare a sulfur-carbon composite.

[0138] Comparative Example 1: Preparation of sulfur-carbon composite

[0139] Carbon nanotubes (trade name: Multiwall CNT, manufacturer: Aldrich Corporation) and sulfur (S8) were uniformly mixed in a weight ratio of 3:7, placed in an oven at 155° C. and treated for 30 minutes to prepare a sulfur-carbon composite.

[0140] Comparative Examples 2 to 4: Preparation of Sulfur-Carbon Composites

[0141] Carbon nanotubes (trade name: Multiwall CNT, manufacturer: Aldrich Corporation) and sulfur (S8) were uniformly mixed in a weight ratio of 3:7, placed in an oven at 155° C. and treated for 30 minutes to prepare a sulfur-carbon composite.

[0142] 10 g of the polyDMA-PEGMEA copolymer prepared in Preparation Example 1 was dissolved in 90 g of distilled water to prepare a coating agent having a concentration of 10 wt %, which was then diluted to be used as a coating agent.

[0143] <Comparative Example 2>

[0144] The coating agent was mixed with 10 g of the prepared sulfur-carbon composite to prepare a polyDMA-PEGMEA copolymer-coated sulfur-carbon composite (weight ratio of sulfur-carbon composite:polyDMA-PEGMEA copolymer=99.5:0.5).

[0145] <Comparative Example 3>

[0146] The coating agent was mixed with 10 g of the prepared sulfur-carbon composite to prepare a poly-DMA-PEGMEA copolymer-coated sulfur-carbon composite (weight ratio of sulfur-carbon composite:poly-DMA-PEGMEA copolymer=99:1).

[0147] <Comparative Example 4>

[0148] The coating agent was mixed with 10 g of the prepared sulfur-carbon composite to prepare a polyDMA-PEGMEA copolymer-coated sulfur-carbon composite (weight ratio of sulfur-carbon composite:polyDMA-PEGMEA copolymer=98:2).

[0149] Comparative Example 5: Preparation of sulfur-carbon composite

[0150] The carbon material coated with the polyDMA-PEGMEA copolymer (monomer molar ratio 5:5) prepared in Preparation Example 5 and sulfur (S8) were uniformly mixed at a weight ratio of 3:7, placed in an oven at 155° C. and treated for 30 minutes to prepare a sulfur-carbon composite.

[0151] Comparative Example 6: Preparation of sulfur-carbon composite

[0152] A carbon material prepared by coating a PEO polymer on a carbon nanotube (trade name: Multiwall CNT, manufacturer: Aldrich Corporation) (weight ratio = 99:1) and sulfur (S8) were uniformly mixed at a weight ratio of 3:7, placed in an oven at 155° C. and treated for 30 minutes to prepare a sulfur-carbon composite.

[0153] Examples 3 to 4 and Comparative Examples 7 to 12: Production of positive electrodes for lithium-sulfur batteries

[0154] 90 wt % of the sulfur-carbon composite prepared in Example 1, Example 2, Comparative Examples 1 to 6 as a positive electrode active material, 5 wt % of DENKA carbon black as a conductive material, and 5 wt % of styrene-butadiene rubber / carboxymethyl cellulose (SBR:CMC=7:3) as a binder were added and mixed to prepare a positive electrode slurry composition.

[0155] The prepared positive electrode slurry composition was coated on an aluminum current collector, dried at 50° C. for 12 hours, and compressed with a roller press to manufacture positive electrodes for lithium-sulfur batteries of Examples 3 to 4 and Comparative Examples 7 to 12, respectively.

[0156] Examples 5 to 6 and Comparative Examples 13 to 18: Production of Lithium-Sulfur Batteries

[0157] Together with the positive electrode prepared in Example 3, Example 4 and Comparative Examples 7 to 12, a lithium metal film having a thickness of 35 μm was used as the negative electrode, and a mixed solution prepared by dissolving 1 M concentration of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and 1 wt % of lithium nitrate (LiNO3) in an organic solvent consisting of 1,3-dioxolane and dimethoxyethane (DOL:DME=1:1 (volume ratio)) was used as the electrolyte to manufacture lithium-sulfur batteries of Examples 5 to 6 and Comparative Examples 13 to 18, respectively.

[0158] Specifically, the prepared positive electrode and negative electrode were placed facing each other, and between them, polyethylene having a thickness of 20 μm and a porosity of 45% was placed as a separator, and then the prepared electrolyte was injected to manufacture a lithium-sulfur battery.

[0159] Table 1

[0160]

[0161] Experimental Example 1: Performance evaluation of lithium-sulfur batteries

[0162] For the lithium-sulfur batteries prepared in Example 5, Example 6, and Comparative Examples 13 to 18, the discharge and charge were repeated for 2.5 cycles at a current density of 0.1C, and the discharge and charge were repeated for 3 cycles at a current density of 0.2C using a charge / discharge measuring device (LAND CT-2001A, Wuhan, China), and then the discharge capacity and coulomb efficiency were measured while discharging at 0.5C and charging at 0.3C to evaluate the life characteristics of the battery. The results obtained at this time are shown in Figure 1 to Figure 5 middle.

[0163] Reference Figure 1 It can be seen that the lithium-sulfur battery of Example 5 comprising the sulfur-carbon composite of Example 1 (the weight ratio of carbon material: poly-DMA-PEGMEA copolymer = 99:1) shows better results in terms of life than the lithium-sulfur battery of Example 6 comprising the sulfur-carbon composite of Example 2 (the weight ratio of carbon material: poly-DMA-PEGMEA copolymer = 98:2).

[0164] Reference Figure 2 It can be seen that the lithium sulfur batteries of Examples 5 and 6 (the surface of the carbon material is coated with a poly-DMA-PEGMEA copolymer) (see Figure 1 ) shows better results in terms of reactivity and lifespan than the lithium-sulfur battery of Comparative Example 13 comprising the sulfur-carbon composite (without coating) of Comparative Example 1.

[0165] Reference Figure 3 It can be seen that the lithium sulfur batteries of Examples 5 and 6 (the surface of the carbon material is coated with a poly-DMA-PEGMEA copolymer) (see Figure 1 ) show better results in terms of reactivity and lifespan than the lithium-sulfur batteries of Comparative Examples 13 to 16 comprising the sulfur-carbon composites of Comparative Examples 2 to 4 (the surface of the sulfur-carbon composite is coated with a poly-DMA-PEGMEA copolymer).

[0166] Reference Figure 4 It can be seen that the lithium-sulfur battery of Example 5 (using a carbon material coating agent with a monomer molar ratio of poly-DMA-PEGMEA copolymer = 3:7) shows better results in terms of reactivity and life than the lithium-sulfur battery of Comparative Example 17 containing the sulfur-carbon composite of Comparative Example 5 (using a carbon material coating agent with a monomer molar ratio of poly-DMA-PEGMEA copolymer = 5:5).

[0167] Reference Figure 5 It can be seen that the lithium-sulfur battery of Example 5 (using polyDMA-PEGMEA copolymer as the carbon material coating agent) shows better results in terms of reactivity and life span than the lithium-sulfur battery of Comparative Example 18 containing the sulfur-carbon composite of Comparative Example 6 (using PEO as the carbon material coating agent).

[0168] From these results, it was confirmed that the lithium-sulfur battery including the sulfur-carbon composite proposed in the present invention has excellent battery reactivity and life characteristics.

Claims

1. A sulfur-carbon composite comprising: a carbon material coated with a copolymer comprising a monomer containing a catechol group and a monomer containing a lithium ion conductor; and sulfur, The monomer containing a lithium ion conductor is at least one selected from a monomer containing an ethyleneoxy group and a monomer containing a sulfone group. The molar ratio of the monomer containing catechol group to the monomer containing lithium ion conductor is 1-5:5-9, The sulfur is selected from inorganic sulfur; Li2S n Wherein n≥1; at least one of the group consisting of disulfide; organic sulfur compound and carbon-sulfur polymer. 2 . The sulfur-carbon composite according to claim 1 , wherein the weight average molecular weight of the copolymer is 5,000 to 1,000,000. The sulfur-carbon composite according to claim 1 , wherein the copolymer is a random copolymer. The sulfur-carbon composite according to claim 1 , wherein the monomer containing a catechol group is a vinyl monomer.

5. The sulfur-carbon composite according to claim 1, wherein the copolymer is represented by the following formula 1: [Formula 1] in R1 and R2 are each independently hydrogen or methyl, a and b represent the molar ratio of each monomer, a is 1 to 5, and b is 5 to 9; and n is a natural number ranging from 1 to 20. 6 . The sulfur-carbon composite according to claim 1 , wherein the carbon material comprises at least one selected from the group consisting of graphite, graphene, carbon black, carbon nanotubes, carbon fibers, carbon nanobelts, carbon nanoribbons, carbon nanorods, and activated carbon. 7 . The sulfur-carbon composite according to claim 1 , wherein a weight ratio of the copolymer including a monomer containing a catechol group and a monomer containing a lithium ion conductor to the carbon material is 0.1:99.9 to 5:

95.

8. A positive electrode for a lithium-sulfur battery, comprising the sulfur-carbon composite according to claim 1.

9. A lithium-sulfur battery comprising a positive electrode; a negative electrode; a separator disposed between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode is the positive electrode according to claim 8.

Citation Information

Patent Citations

  • The acrylic binder for the manufacturing of cathode of lithium sulfur secondary battery and the usage thereof

    KR1020180033665A

  • Apparatus and method for sensing the rear and side of a vehicle

    KR1020190064310A

  • A road cutting machine

    KR1020200064835A